ANALISIS KEPUASAN KERJA BERDASARKAN MOTIVASI, LINGKUNGAN DAN KEMAMPUAN KERJA (Studi pada Pegawai Lapas Kelas IIB Bireuen) - Ibrahim, Ibrahim; Hanafi Wahyudi, Muhammad; Iskandar, Raihan (LPPM-UNIKI, 2024)
The research aims to empirically analyze employee job satisfaction in relation to internal and external factors, namely work motivation, work environment and employee abilities. Using a survey method of 59 Class IIB Bireuen prison employees with associative quantitative research. And data analysis with inferential statistics, namely the path analysis model. The results of the analysis found that; (1) employee job satisfaction is significantly influenced by motivation factors by 44.57%, work environment factors by 53.17% and work ability by 61.2%. (2) Contribution Together, motivation, environmental and work ability factors contribute to employee job satisfaction, amounting to 59.10%. (3). There is a causal relationship between exogenous variables, namely work motivation, work environment and work ability.